Incidence, prevalence, and trend analysis of the use of insulin delivery systems in the United States (2005 to 2011). (May 2015) - Perez-Nieves, Magaly; Jiang, Dingfeng; Eby, Elizabeth
Abstract Objective: Estimate the incidence and prevalence rates and assess overall trends among patients with diabetes using insulin vial/syringe and pens over time. Methods: A retrospective study was conducted using the Truven MarketScan database from 1 July 2004 to 31 December 2011. The database contained medical and pharmacy claims of >20 million US residents insured by commercial health plans. Patients with diabetes who utilized vial/syringe and pens were included. Incidence rate was defined as the proportion of patients initiating a new insulin type for the first time with vial/syringe and pens within each year from 2005 to 2011 among the total number of patients initiating that particular insulin type for the first time. Prevalence rate was defined as the proportion of patients using vial/syringe or pens among patients with diabetes using that insulin type within each year from 2005 to 2011. A linear trend over time was assessed by Cochran–Armitage Trend tests and Generalized Estimating Equations. Results: Incidence of patients initiating vial/syringe decreased from 2005 to 2011 (basal analog [90.5% to 31.3%]; mealtime analog [67.6% to 37.1%]), while patients initiating pens increased (basal analog [9.5% to 68.7%]; mealtime analog [32.4% to 62.9%]). There was a significant trend over time indicating increased usage of pens relative to vial/syringe; the number of pen users increased (all p < 0.0001 except mealtime human). Prevalence of patients using vial/syringe decreased from 2005 to 2011 (basal analog [93.8% to 41.2%]; mealtime analog [71.0% to 50.6%]), while patients using pens increased (basal analog [6.2% to 58.8%]; mealtime analog [29.0% to 49.4%]). From 2005 to 2011, patients were more likely to use pens than vial/syringe (all p < 0.0001 except for human mixtures and mealtime human). Conclusions: The incidence and prevalence of patients using the traditional vial/syringe decreased over time, while the use of pens increased. Some patient populations may be under-represented, limiting generalizability of results.